Strategi Guru BK dan Wali Kelas dalam Menangani Siswa Bermasalah di SMP Negeri 4 Medan - Aloi Hasugian; Dosta Ernauli Siregar; Sabrina Nur Karimah Nasution; Tessalonika Purba (Lembaga Pengembangan Kinerja Dosen, 2025)
This research analyzes the strategies and collaboration between guidance and counseling teachers and homeroom teachers in addressing problematic students at SMP Negeri 4 Medan. The background of this study highlights the importance of guidance and counseling services in supporting students’ personal and social development, especially during the critical transition period in junior high school. However, the implementation of these services often encounters obstacles such as negative perceptions, lack of formal guidelines, and professional challenges. Using a qualitative descriptive method through interviews, observations, and documentation, the research reveals that effective strategies include building positive relationships, early detection, preventive and curative interventions, and open communication with parents. The synergy between guidance and counseling teachers and homeroom teachers, through regular information exchange and coordinated intervention planning, significantly improves the management of problematic students. Nevertheless, challenges such as limited time, differences in role perceptions, and lack of structured communication forums still hinder optimal collaboration. The study concludes that comprehensive and coordinated collaboration is essential for effective management of student problems in schools.